Spectroscopic Studies on 39-Ca for Classical Nova Endpoint Nucleosynthesis - Liang, Johnson (My University, 2020)
In classical novae, the endpoint of nucleosynthesis occurs near A ~ 40. Currently, observations of classical novae predict an order of magnitude enhancement of endpoint elements, such as Ar, K, and Ca, relative to solar abundances; however, simulations predict abundances closer to that of solar abundances. A sensitivity study examining the effect of reaction rates on the abundances of these elements has shown that the reaction 38-K(p,g)39-Ca can change the abundances of endpoint nuclides by an order of magnitude or more. In temperatures characteristic of this environment, this reaction rate is dominated by l =0 resonance reactions within the Gamow window. These correspond to states in 39-Ca with spin-parity of 5/2+ and 7/2+ between Ex = 6.0−6.5 MeV . While a direct measurement was carried out for these states, more precise values for the excitation energies were recommended. In this work high resolution spectroscopic studies of 39-Ca were carried out to provide more information on the various resonances that lie in the Gamow window, and illuminate additional undiscovered states. The first study was conducted at the Maier- Leibnitz-Laboratory (MLL), employing the 40-Ca(d,t)39-Ca reaction, and the follow up study was conducted at the Triangle Universities Nuclear Laboratory (TUNL) using the 39-K(3-He,t)39-Ca reaction. The method and apparatus are discussed in this work. Energy levels in 39-Ca with 10 keV uncertainties had uncertainties reduced to 3-4 keV. In addition, several new states were found in 39-Ca from the TUNL experiment. Finally, there is an ~ 10 keV systematic difference between previously evaluated states and the states measured in this work - a factor that affects the direct measurement carried out previously. This factor in combination with the results of this work show that the reaction rate of this may be higher than previously thought, and have a higher impact on the final abundances of elements synthesized in classical novae.
Keywords: Nuclear Astrophysics